Stabilometry in Relation to Hip and Knee Muscle Force in Children with Surgically Treated Unilateral Slipped Capital Femoral Epiphysis - Marius Negru; Anca Raluca Dinu; Elena Amaricai; Liliana Catan; Andrei Daniel Bolovan; Adrian Emil Lazarescu; Corina Maria Stanciulescu; Eugen Sorin Boia; Calin Marius Popoiu (Children)
Background/Objectives: The main aim of our study was to analyze the stabilometric parameters in relation to hip and knee muscle force in children with unilateral slipped capital femoral epiphysis (SCFE) who had undergone surgical treatment. Another objective was to compare the stabilometry in three testing situations (eyes open, eyes closed, and head retroflexed). Methods: In total, 26 patients with unilateral right SCFE treated via in situ fixation with one percutaneous screw performed stabilometry assessments under three different situations (with their eyes open, with their eyes closed, and with their head retroflexed) and isometric muscle force assessment of the bilateral hip flexors, extensors, abductors and adductors and bilateral knee flexors and extensors. Results: No significant differences between the right side (affected hip) and left side (non-affected hip) were recorded for all of the tested muscle groups. We found significant negative correlations between the 90% confidence ellipse area (eyes open condition) and left knee extensors (p = 0.028), right knee flexors (p = 0.041), and left knee flexors (p = 0.02), respectively. When performing the comparison between the eyes open and eyes closed situations, there were significant differences in CoP path length (p < 0.0001) and maximum CoP speed (p = 0.048); the parameters increased in the eyes closed situation. Conclusions: Better postural stability is acquired when assessed with eyes open or with the head retroflexed in contrast with eyes closed testing.